DESIGN OF EXPERIMENTS-GUIDED EXTRACTION OF BIOACTIVE FLAVONOIDS FROM PSIDIUM GUAJAVA L. LEAVES: ANTIOXIDANT AND CYTOTOXIC EVALUATIONS - RENUKADEVI J; SAM HELINTO J; PRENA D; AROCKIYA RABIN A; JOYAL S; GOHULRAM S; THRISHA S (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objectives of the study are to optimize the Soxhlet extraction of flavonoids from guava leaves and evaluate the antioxidant and anticancer potential of the extract. Methods: Extraction parameters such as solvent volume, temperature, and time were optimized using response surface methodology based on a Box–Behnken design. Phytochemical profiling was conducted using preliminary screening, thin-layer chromatography, ultraviolet-visible spectrophotometry, and high-performance liquid chromatography to confirm the presence of quercetin. Antioxidant activity was assessed through 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, reduced glutathione (GSH), glutathione peroxidase (GPx), and glutathione S-transferase (GST) assays. Cytotoxicity against HeLa cervical cancer cells was evaluated using the MTT assay and DNA fragmentation analysis. Results: Optimization improved flavonoid extraction efficiency. Phytochemical analysis confirmed the presence of quercetin. The extract exhibited strong antioxidant activity, evidenced by high DPPH scavenging and increased levels of GSH, GPx, and GST. The MTT assay showed significant antiproliferative activity against HeLa cells, with an IC50 of 9.36 μg/mL. DNA fragmentation indicated apoptosis induction. Conclusion: The optimized Soxhlet extraction effectively enhances flavonoid yield from Psidium guajava leaves. The extract demonstrates notable antioxidant and anticancer properties, highlighting its promise as a candidate for pharmaceutical and nutraceutical applications.